New genetic prognostic biomarkers in primary central nervous system lymphoma (PCNSL) - Diego Gomes Candido Reis; Débora Levy; Luís Alberto de Pádua Covas Lage; Hebert Fabrício Culler; Vanderson Rocha; Sérgio Paulo Bydlowski; Maria Cláudia Nogueira Zerbini; Juliana Pereira (Brain and Behavior, 2021)
Abstract Background PCNSL is a rare extranodal NHL with poor prognosis. Tumorigenesis has been associated with hyperactivation of BCR downstream and NFkB pathways. We studied the prognosis of the relative expression profile of target genes of NFkB pathway (MYC, BCL2), the essential transcriptional regulator in hematopoiesis LMO2, the checkpoint regulation pathway MGMT, the transcription factor POU2F1, the immune checkpoint gene PDCD1, and the proto‐oncogene and transcriptional repressor gene BCL6 and its proteins in PCNSL. Methods This study is a retrospective cohort study; 35 immunocompetent PCNSL‐DLBCL patients had their gene expression (RT‐qPCR) normalized to internal control gene GUSB. Results Median patient age was 62 years, median OS was 42.6 months (95% CI: 26.6–58.6), PFS was 41 months (95% CI: 19.7–62.4), and DFS was 59.2 months (95% CI 31.9–86.6). A moderate correlation was found between the gene/protein expressions of MYC (kappa = 0.596, p = .022) and of BCL2 (kappa = 0.426, p = .042). Relative gene expression of MYC ≥ 0.201 (HR 6.117; p = .003) was associated with worse 5‐year OS. Relative gene expression of MYC ≥ 0.201 (HR 3.96; p = .016) and MGMT ≥ 0.335 (HR 3.749; p = .056) was associated with worse PFS. Age > 60 years and IELSG score moderate/high were also associated with worse prognosis. Conclusions Overexpression of MYC and overexpression of MGMT were prognostic markers associated with unfavorable clinical outcomes in PCNSL.